2011
DOI: 10.1002/mabi.201000401
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Sensitive Pentablock Copolymer Nanocapsules as Nontoxic and Efficient Gene Carriers

Abstract: A biodegradable amphiphilic pentablock copolymer PAE-PCL-PEG-PCL-PAE with a pH-sensitive unit was synthesized for use as a nontoxic, biodegradable carrier for gene delivery by forming nanocapsules entrapping nucleic acid drugs. The PAE block can interact with plasmid DNA to form polyelectrolyte complexes in an acidic environment. At physiological pH, the PAE blocks are deprotonated and form an insoluble skin, resulting in the formation of nanocapsules that encapsulate plasmid DNA. The surface charges of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Poly(β-amino ester) (PAE), which is noncytotoxic and forms a good complex with negatively charged proteins or pDNA at physiological pH, was introduced as a cationic, biodegradable polymer. Aqueous solutions of PAE–PCL–PEG–PCL–PAE (Figure B) undergo a sol-to-gel transition as a function of both pH and temperature (Figure A). The degradation rates of these gels can be tuned by replacing the hydrophobic PCL blocks with the less hydrophobic PCLA. Graft copolymer of (PAE- g -PCL)–PEG–(PAE- g -PCL) exhibited a different gelation window than the linear PAE–PCL–PEG–PCL–PAE copolymers .…”
Section: Injectable Ph- and Temperature-sensitive Hydrogelsmentioning
confidence: 99%
“…Poly(β-amino ester) (PAE), which is noncytotoxic and forms a good complex with negatively charged proteins or pDNA at physiological pH, was introduced as a cationic, biodegradable polymer. Aqueous solutions of PAE–PCL–PEG–PCL–PAE (Figure B) undergo a sol-to-gel transition as a function of both pH and temperature (Figure A). The degradation rates of these gels can be tuned by replacing the hydrophobic PCL blocks with the less hydrophobic PCLA. Graft copolymer of (PAE- g -PCL)–PEG–(PAE- g -PCL) exhibited a different gelation window than the linear PAE–PCL–PEG–PCL–PAE copolymers .…”
Section: Injectable Ph- and Temperature-sensitive Hydrogelsmentioning
confidence: 99%
“…For example, take the normally applied concentration of polymer (1000 μg/mL) in vivo derived from activated ester polymer precursors. If up to 10% active esters are left after postpolymerization modification, cell viability showed that cells treated with P2 decreased to 92%, which did not induce serious cytotoxic effect and this toxicity level is still acceptable as biocompatible gene carriers . In contrast, at the same concentration, the cell viability for PPF ester polymer samples decreased to 78% (Figure , gray filled pattern region).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…In order to maximize the therapeutic effect, overstable micelles are not desirable since the release of the drug might be inhibited when the micelles arrive at the site of action. Therefore, various stimuli‐responsive drug nanocarriers were developed to overcome the problems and achieve smart drug release . In general, fast drug release can be achieved if the core of the micelles becomes hydrophilic under different stimulus since the micelles will be disassembled .…”
Section: Introductionmentioning
confidence: 99%